The Effectiveness of Spiritual Parenting Training in Enhancing Parental Self-Efficacy among Working Mothers - Ihda Al Husnayaini; Syamsul Bachri Thalib; M. Ahkam Alwi; Ahmad Razak; Abdul Saman (Indonesian Journal of Learning Education and Counseling, 2026)
Working mothers face various role demands in their lives, making them more susceptible to role conflicts that can affect their self-confidence in providing parenting and education to their children, also known as parental self-efficacy. One of the factors that influences the level of parental self-efficacy is their knowledge and values of beliefs. Spiritual parenting training is one of the efforts aimed at increasing parental self-efficacy. This study aims to examine the effectiveness of spiritual parenting training as an effort to increase parental self-efficacy in working mothers in Makassar City. This study used a quasi-experimental design with a one-group pre-test post-test model involving 10 participants. The measuring instrument used was the parental self-efficacy scale with a reliability value of 0.990. The results of the study reveal an increase in parental self-efficacy with an average pre-test score of 102 and a post-test score of 128. Data analysis was conducted using the Wilcoxon signed rank test technique with a significance value of 0.0025 (p < 0.05). The spiritual parenting training increases awareness of the importance of mothers’ roles and the commitment to parenting, which has an impact on the increase of parental self-efficacy of working mothers in Makassar City.